Formation ability and drug resistance mechanism of Klebsiella pneumoniae biofilm and capsule for multidrug-resistant : K. pneumoniae biofilm and capsule for multidrug-resistant - Liang, Jiayu; Lin, Shanshan; He, Lanbo (Cellular and Molecular Biology, 2023)
This study was to explore the formation ability of biofilm and capsule and the drug resistance mechanism for multidrug-resistant Klebsiella pneumoniae. firstly, 55 strains of K. pneumoniae were screened out from the body fluid specimens of the laboratory. The strains were drug-resistant, and the characteristics of clinical infections of these strains were analyzed. Secondly, all strains were tested for the presence of biofilms and capsules, and then the deoxyribonucleic acid (DNA) genomes of the strains extracted were detected using polymerase chain reaction (PCR) technology. Finally, the serotype genes and virulence genes of the strains were screened, and the relationship between these two genes and the formation of capsules and biofilms was analyzed and compared. A new generation of sequencing technology was applied to analyze the genome structure of K. pneumoniae, comparative genomics technology was adopted to analyze the drug resistance plasmids, and molecular cloning and other methods were utilized to clone the drug resistance-related genes. of the 55 strains of K. pneumoniae isolated clinically, 61.8% came from blood with a total number of 34 strains; 8 strains were from secretion specimens (accounting for 14.5% of the total); and 7 strains were from drainage fluid (accounting for 12.7% of the total), including 2 strains from pus, bile, and pleural fluid, respectively. The strains were tested by PCR, of which iroN virulence genes were the most (34 strains), accounting for 61.8%, followed by wabG and fimH (33 strains, accounting for 60% of the total), followed by magA, K2, K20, K1, and K57. The positive rates of the two virulence genes (fimH and wabG) were higher in positive strains of biofilm. The drug susceptibility results showed that ampicillin and amoxicillin were more resistant to capsule-positive strains than the capsule-negative strains. K. pneumoniae had been able to form a complete capsule and biofilm, the formation rate of biofilm was higher than that of the capsule, and there was an increasing trend. The two serotype genes (K20 and K2) accounted for relatively high proportions, and K. pneumoniae carried relatively more virulence genes (wabG and fimH), which may be closely related to the capsule production of K. pneumoniae. In addition, resistance-related genes were also transferred horizontally in different strains of bacteria, forming a wide range of drug resistance, which brought great difficulties to clinical work.